2020
DOI: 10.1177/1359105319897783
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic and psychosocial correlates of resilience among older adults living with HIV in the Deep South

Abstract: This cross-sectional study assessed the psychosocial and sociodemographic correlates of resilience among older adults living with HIV. Data were obtained from 103 men and 53 women aged 50 years and older in South Carolina. Multivariable linear regression models showed that employment (any) ( B: 3.52; 95% confidence interval : 1.04, 5.99), education ( B: −3.56; 95% confidence interval : −6.15, −0.98), time since diagnosis ( B: 0.18; 95% confidence interval : 0.04, 0.31), and social support ( B: 0.27; 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
2
5
0
Order By: Relevance
“…The goal of this study was to examine the association of We found that age, race, gender, and substance use were not associated with resilience or HRQoL among older PLWH, which supports prior work suggesting that resilience is possible across diverse contexts (Brewer et al, 2020;Chmitorz et al, 2018;Emlet et al, 2011;Fazeli et al, 2019;Fontes and Neri, 2015;Furlotte and Schwartz, 2017). We found an association with higher resilience and higher SES, which consistent with prior work in older PLWH (Brown et al, 2021), suggests that higher income and education levels may provide resources that afford PLWH to foster resilience strategies, such as health behaviors, and also positions those with greater resources to live in contexts with less stress (Emlet et al, 2017;Fazeli et al, 2019;Vance et al, 2016Vance et al, , 2019Worthington and Krentz, 2005). The lack of association between HIV severity and resilience and HRQoL is consistent with some prior work showing that psychosocial factors such as selfrated successful aging was unrelated to disease severity (Moore et al, 2013), although some studies have found associations between resilience and HIV outcomes such as CD4 count (Moore et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The goal of this study was to examine the association of We found that age, race, gender, and substance use were not associated with resilience or HRQoL among older PLWH, which supports prior work suggesting that resilience is possible across diverse contexts (Brewer et al, 2020;Chmitorz et al, 2018;Emlet et al, 2011;Fazeli et al, 2019;Fontes and Neri, 2015;Furlotte and Schwartz, 2017). We found an association with higher resilience and higher SES, which consistent with prior work in older PLWH (Brown et al, 2021), suggests that higher income and education levels may provide resources that afford PLWH to foster resilience strategies, such as health behaviors, and also positions those with greater resources to live in contexts with less stress (Emlet et al, 2017;Fazeli et al, 2019;Vance et al, 2016Vance et al, , 2019Worthington and Krentz, 2005). The lack of association between HIV severity and resilience and HRQoL is consistent with some prior work showing that psychosocial factors such as selfrated successful aging was unrelated to disease severity (Moore et al, 2013), although some studies have found associations between resilience and HIV outcomes such as CD4 count (Moore et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…There are limited studies examining the association of resilience and HRQoL among middle-aged and older PLWH in the Deep South, a subpopulation that experiences unique stressors (Blake et al, 2017; Watson et al, 2019). One recent study among 156 older PLWH in the Deep South found that employment, education, time since diagnosis, and social support were significant correlates of resilience in a multivariable model (Brown et al, 2021). Similarly, a study of 100 Black women living with HIV (age range 22–67) in the Southeast found that resilience was associated with lower depressive symptoms and lower trauma symptoms (Dale et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We also searched the Open Grey database for grey literature but did not find any relevant articles. After removing duplicates and screening the articles by the eligibility criteria, 166 articles were included in the review [ 6 , 20 , 22 , 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The included studies recruited a total of 68,933 participants, with individual sample sizes ranging from 14 in Rwanda [ 98 ] to 2987 in China [ 187 ]. The recruited participants included diverse samples of PLWH, including adolescents and young adults living with HIV in 12 studies [ 22 , 23 , 38 , 62 , 72 , 80 , 83 , 125 , 126 , 129 , 163 , 178 ], adolescent girls and young women living with HIV in four studies [ 33 , 54 , 68 , 117 ], pregnant women living with HIV in one study [ 31 ], older women living with HIV in one study [ 151 ], older adults living with HIV in seven studies [ 44 , 61 , 63 , 77 , 81 , 139 , 161 ], women living with HIV in 19 studies [ 25 , 42 , 50 , 57 , 58 , 59 , 89 , 90 , 110 , 123 , 135 , 136 , 138 , 141 , 157 , 158 , 168 , 169 , 179 ], men living with HIV in six studies [ 46 , 75 ,…”
Section: Resultsmentioning
confidence: 99%
“…Extroverts experience higher well-being (Diener & Ryan, 2009;Keyes et al, 2002;Krastev & Yordanova, 2012) than introverts that may be related to extroverts' directedness towards other people, because positive relationships are regarded as a dimension of well-being (Ryff & Keyes, 1995) and a pre-requisite for well-being (Mizova et al, 2010). Well-being increases with reduction of neuroticism (Diener & Ryan, 2009;Diener & Seligman, 2002;Keyes et al, 2002;Zarbova, 2019) that may be because emotional stability predisposes towards mental resilience (Bozhilova, 2013) and mental resilience improves many types of well-being (Brown et al, 2020;Burns et al, 2011) and global well-being in this way. These connections between well-…”
Section: Discussionmentioning
confidence: 99%